Impact of fleQ Deficiency on Resource Allocation and Heterologous Gene Expression in Pseudomonas putida Across Various Growth Media - Junyoung Kim; Sooyeon Lee; Alexander P. S. Darlington; Juhyun Kim (Microbial Biotechnology)
ABSTRACT Pseudomonas putida is widely used in industrial applications, including the recombinant proteins production, because of its natural advantageous properties. In this study, the gene encoding FleQ, the primary regulator of flagellar synthesis, was deleted to construct a new non‐motile P. putida KT2440‐derived strain (ΔfleQ). The non‐motile cells showed reduced biofilm formation and enhanced expression of a heterologous gene in nutrient‐rich media compared with the wild‐type (WT) strain, attributed to the reallocation of cellular resources from flagellar synthesis and cellular motility. Additionally, the ΔfleQ strain exhibited enhanced tolerance to chloramphenicol, indicating higher ribosome production, confirmed by a higher RNA/protein ratio relative to the WT. While the WT strain showed decreased growth and a three‐fold increase in reporter gene activity in minimal media, the ΔfleQ strain maintained consistent reporter gene expression and exhibited a relatively higher growth rate. This suggests that the FleQ is involved in modulating proteome allocation based on nutrient quality. The removal of FleQ allows for more flexible resource allocation, creating a chassis strain with nutrient quality‐independent gene expression capacity, which could be valuable in industrial applications where consistent output is essential.